An encapsulated Yersinia pseudotuberculosis is a highly efficient vaccine against pneumonic plague. - Anne Derbise; Alba Cerdà Marín; Patrick Ave; Thierry Blisnick; Michel Huerre; Elisabeth Carniel; Christian E Demeure (Public Library of Science (PLoS), 2012)
BACKGROUND: Plague is still a public health problem in the world and is re-emerging, but no efficient vaccine is available. We previously reported that oral inoculation of a live attenuated Yersinia pseudotuberculosis, the recent ancestor of Yersinia pestis, provided protection against bubonic plague. However, the strain poorly protected against pneumonic plague, the most deadly and contagious form of the disease, and was not genetically defined. METHODOLOGY AND PRINCIPAL FINDINGS: The sequenced Y. pseudotuberculosis IP32953 has been irreversibly attenuated by deletion of genes encoding three essential virulence factors. An encapsulated Y. pseudotuberculosis was generated by cloning the Y. pestis F1-encoding caf operon and expressing it in the attenuated strain. The new V674pF1 strain produced the F1 capsule in vitro and in vivo. Oral inoculation of V674pF1 allowed the colonization of the gut without lesions to Peyer's patches and the spleen. Vaccination induced both humoral and cellular components of immunity, at the systemic (IgG and Th1 cells) and the mucosal levels (IgA and Th17 cells). A single oral dose conferred 100% protection against a lethal pneumonic plague challenge (33×LD(50) of the fully virulent Y. pestis CO92 strain) and 94% against a high challenge dose (3,300×LD(50)). Both F1 and other Yersinia antigens were recognized and V674pF1 efficiently protected against a F1-negative Y. pestis. CONCLUSIONS AND SIGNIFICANCE: The encapsulated Y. pseudotuberculosis V674pF1 is an efficient live oral vaccine against pneumonic plague, and could be developed for mass vaccination in tropical endemic areas to control pneumonic plague transmission and mortality.